(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, students can develop creative thinking skills, creative thinking skills that help them make confident decisions and quickly acquire new knowledge for success, improve people’s lives through new ideas, connect people and opportunities, or there is talk of harmonizing.